An exploratory randomised controlled trial evaluating text prompts in Lebanon to encourage health‐seeking behaviour for hypertension. Issue 2 (27th August 2020) - Schmidtke, K. A.; Vlaev, I.; Kabbani, S.; Klauznicer, H.; Baasiri, A.; Osseiran, A.; El Rifai, G.; Fares, H.; Saleh, N.; Makki, F.
Abstract: Aims of the study: The current study evaluates the effectiveness of an opportunistic mobile screening on the percentage of people who are aware of whether they may be hypertensive (in an observational study) and the effectiveness of reminder prompts on the percentage of people who seek further medical attention (in a randomised controlled trial). Methods used to conduct the study: The screening of 1227 participants (529 female) was conducted during the registration period of the 2018 Beirut International Marathon in Lebanon. Next, 266 participants whose screening indicated hypertension (64 Female) were randomly allocated to a treatment group or a control group in a 1:1 fashion. The treatment group received a reminder prompt to seek further medical attention for their potential hypertension and the control group did not. The overt nature of the text message meant that participants in the treatment group could not be blinded to their group allocation. The primary outcome is participants' self‐reports of whether they sought further medical attention. Results of the study: For the opportunistic screening, a 25% prevalence rate and a 24% awareness rate of hypertension was indicated. A McNemar analysis suggested that the screening increased participant awareness ( X 2 (N = 1227) = 72.16, P < .001). For the randomised controlled trial, 219 participants provided follow‐up data via a phone call (82% retention). A Chi‐squared analysis suggested that the reminder prompt successfully encouraged more participants to seek further medical attention, 45.5% treatment group vs 28.0% control group ( X 2 (1, N = 219) = 7.19, P = .007, φ = 0.18). Conclusions drawn and clinical implications: Extra support in the form of a brief reminder message can increase the percentage of people who seek further medical attention after attending an opportunistic screening at a marathon event. The discussion reviews how the results align with previous research, strengths and limitations of the current study, and implications for future research and practice.